Reviews on Plants Gum and Mucilage I: The Composition and Pharmacological Significance of Turmeric (Curcuma longa) Rhizomes Polysaccharides and Mucilage/their Aqueous Extracts Commercial Products - Hussein A. H AlSaidy; Dhurgham A.H. Alhasan; Ali A. Ali (University of Thi-Qar Journal of Science, 2021)
The utilization of plants’ polysaccharide as hydrocolloid materials within the last four decades, had drawn a significant attention due to their therapeutic and pharmaceutical applications. Among the Zingiberaceae family of plants, Curcuma longa L. rhizomes polyphenolic product like curcuminoids, flavonoids, turmerones and other polyphenolics had gained extensive investigation efforts and reported intensively. Curcuma longa L. rhizomes polysaccharide type mucilage hasn’t received considerable attention by academic authors and researchers. In this survey, we tried to highlight this type of phytomolecules through exploring the issued research articles focusing on their pharmacological importance. Reference books, Scopus, PubMed, Web of Science bibliographic databases and Google scholar scientific search engines besides other open access researches sited on Google were screened for plant polysaccharides significances and uses in addition to their pharmacological activities. Screening was done using six different groups of keywords. All results found by keywords were reviewed and none-relevant articles were excluded by outcome of interests and researcher boundaries of study through a systematic method. It has been stated that, both mucilage and gums types of plants’ polysaccharides had gained great investigation efforts in recent years. Concerning C. longa L. rhizomes; four different polysaccharides had been reported. They were to be isolated, purified and characterized from their polysaccharide mucilage aqueous extract then labelled as Ukonans A, B, C and D. Several biological influences were studied for these polysaccharide compounds and mixtures as well as for their aqueous extracts fractions, including immune busting, anti-inflammatory, anti-ulcerogenic agent, insulin mimetic hypoglycemic agent, anticancer/chemo-preventive and anti-obesity agent activities. Reviewed articles encouges us to conclude the potentiality of investigation of turmeric polysaccharides as pharmaceutical additive/and or co-therapy for several pathological conditions.